PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT DAN FAKTOR –FAKTOR YANG MEMPENGARUHI (Studi Empiris Pada Auditor di Kantor Akuntan Publik Semarang dan Yogyakarta ) - Tri Retno Wulandari; Siti Nor Hikmah (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2012)
The objectives of this research is to test the effect of time pressure, audit risk, materiality, review procedure and quality control, self esteem on premature sign off of audit procedure. This analyze with used the logistic regression is α=5%.  The result of this research indicates that there is a priority sequence of discontinued audit procedure in time pressure conditions. The audit procedure which is often omitted is understanding business's client and the audit procedure which is seldom omitted is physical examination. The logistic regression shows that audit risk, review procedure and quality control have an effect on prematurly signed off  of audit procedure. But time pressure, materiality, self esteem  have not an effect on prematurly signed off  of audit procedure. Keywords : Premature Sign off of Audit Procedure, Time Pressure, Audit Risk, Materialitas, Review Procedure and Quality Control , Self Esteem